Endemic and cosmopolitan fungal taxa exhibit differential abundances in total and active communities of Antarctic soils. (22nd February 2019) - Cox, Filipa; Newsham, Kevin K.; Robinson, Clare H.
Summary: Our understanding of the diversity and community dynamics of soil fungi has increased greatly through the use of DNA‐based identification. Community characterization of metabolically active communities via RNA sequencing has previously revealed differences between 'active' and 'total' fungal communities, which may be influenced by the persistence of DNA from nonactive components. However, it is not known how fungal traits influence their prevalence in these contrasting community profiles. In this study, we coextracted DNA and RNA from soil collected from three Antarctic islands to test for differences between total and active soil fungal communities. By matching these geographically isolated fungi against a global dataset of soil fungi, we show that widely dispersed taxa are often more abundant in the total community, whilst taxa restricted to Antarctica are more likely to have higher abundance in the active community. In addition, we find that active communities have lower richness, and show a reduction in the abundance of the most dominant fungi, whilst there are consistent differences in the abundances of certain taxonomic groups between the total and active communities. These results suggest that the views of soil fungal communities offered by DNA‐ and RNA‐based characterization differ in predictable ways.